Design of short time duty permanent magnet electrical machines - Sciascera, Claudio (2017)
Recent progresses of the aviation industry toward the More Electric Aircraft have increased the demand for high performance Electro-Mechanical Actuators. In this context, extensive research is being conducted for the design of high torque density electrical machines able to meet the high reliability standards required. For low-rate duty applications (e.g. landing gear extension, retraction and steering; flight control surfaces), this can be achieved also by exploiting the characteristic that the motor does not reach a thermal equilibrium. In this work, the principal aim is to investigate the main limits in the design of low-rate duty, high torque density electrical machines and to propose methods for the improvement of the performance and reliability of such machines. This is achieved through detailed analysis of the motor design issues, of its thermal performance, as well as of the most critical ageing phenomena during operations. A structured design procedure for surface mounted permanent magnet machines is presented. A novel thermal model which features high accuracy and low computational cost is presented. A novel winding insulation lifetime consumption model which relates the winding time to failure to its temperature profile during operations is proposed. As vessel to address the thesis’ objectives, a fault tolerant electrical machine, which is an integral part of an actuator for the extension and retraction of a helicopter landing gear, is designed, built and experimentally tested. The tests are aimed at validating the design procedure and the thermal model accuracy. A series of accelerated ageing tests is conducted on samples of the motor windings, which serve to analyse the insulation degradation processes under different stress levels and to validate the proposed lifetime consumption model.